FABRICATION AND CHARACTERIZATION OF A CD²⁺ ION SELECTIVE ELECTRODE OF THE COATED WIRE BASED ON POLYVINYL CHLORIDE - Tentriati Cahaya; Aman Sentosa Panggabean; Moh. Syaiful Arif (JURNAL ATOMIK, 2026)
This study reports the fabrication and characterization of a Cd²⁺ ion-selective electrode of the coated wire (ISE) based on PVC with sodium sulfide as the ionophore. The electrode was prepared using the optimum composition of Na₂S:PVC:DOP (0.7 g:0.2 g:0.1 mL) and doped in Cd(CH₃COOH)₂ solution. The results showed a Nernstian slope of 9.5 mV/decade, detection limit of 1×10⁻⁵ M, optimum pH range of 6–7, response time of 20–60 s, and a lifetime of 3 days. FT-IR analysis demonstrated successful electrode characterization via the formation of Cd–S interactions, indicated by the band at 612.75 cm⁻¹. The electrode exhibited good selectivity toward Cd²⁺ over interfering ions (Zn²⁺, Cu²⁺, NO₃⁻, Cl⁻, SO₄²⁻).